Breaking Barriers: A comparative analysis of the challenges faced by women in traditional leadership positions in South Africa and Zimbabwe - Muleya, A.; Mothoagae, . (Journal of Ecohumanism, 2025)
This concept paper confers a comparative analysis of the obstacles encountered by women in conventional leadership positions in different cultures within South Africa and Zimbabwe. Despite tremendous strides in the direction of gender equality, women still face systematic obstacles that hinder their rise into leadership roles. This article emphasizes the cultural, social, and institutional elements that play a role in these challenges, using existing material from various geographic locations. The analysis shows that cultural norms, gender biases, and Intersectional identities significantly affect women’s experiences in leadership, creating distinct challenges that differ among various societies. Moreover, the emotional demands linked to leadership positions disproportionately impact women, making it difficult for them to manage these challenges efficiently. This study utilizes a systematic literature review (SLR) to investigate the obstacles women encounter in traditional leadership roles in South Africa and Zimbabwe. The literature review adhered to a systematic and clear approach to guarantee the incorporation of pertinent and reliable sources. The results highlight the need for customized strategies considering the unique cultural factors affecting women’s leadership experiences. By cultivating inclusive settings and encouraging gender equality, organizations can establish routes for women’s progress in leadership positions. This study seeks to add to the current dialogue on women’s leadership by recognizing prevalent challenges and suggesting future research paths that delve deeper into the intersection of gender and leadership in various cultures.